Cortical thinning and accumulation of large cortical pores in the tibia reflect local structural deterioration of the femoral neck - Iori, Gianluca; Schneider, Johannes; Reisinger, Andreas; Heyer, Frans; Peralta, Laura; Wyers, Caroline; Glüer, Claus C.; van den Bergh, J.P.; Pahr, Dieter; Raum, Kay (Bone (New York, N.Y.), 2020)
Cortical bone thinning and a rarefaction of the trabecular architecture represent possible causes of increased femoral neck (FN) fracture risk. Due to X-ray exposure limits, the bone microstructure is rarely measurable in the FN of subjects but can be assessed at the tibia. Here, we studied whether changes of the tibial cortical microstructure, which were previously reported to be associated with femur strength, are also associated with structural deteriorations of the femoral neck. The cortical and trabecular architectures in the FN of 19 humans were analyzed ex vivo on 3D microcomputed tomography images with 30.3 μm voxel size. Cortical thickness (Ct.Thtibia), porosity (Ct.Potibia) and pore size distribution in the tibiae of the same subjects were measured using scanning acoustic microscopy (12 μm pixel size). Femur strength during sideways falls was simulated with homogenized voxel finite element models. Femur strength was associated with the total (vBMDtot; R2 = 0.23, p < 0.01) and trabecular (vBMDtrab; R2 = 0.26, p < 0.01) volumetric bone mineral density (vBMD), with the cortical thickness (Ct.ThFN; R2 = 0.29, p < 0.001) and with the trabecular bone volume fraction (Tb.BV/TVFN; R2 = 0.34, p < 0.001), separation (Tb.SpFN; R2 = 0.25, p < 0.01) and number (Tb.NFN; R2 = 0.32, p < 0.001) of the femoral neck. Moreover, smaller Ct.Thtibia was associated with smaller Ct.ThFN (R2 = 0.31, p < 0.05), lower Tb.BV/TVFN (R2 = 0.29, p < 0.05), higher Tb.SpFN (R2 = 0.33, p < 0.05) and lower Tb.NFN (R2 = 0.42, p < 0.01). A higher prevalence of pores with diameter > 100 μm in tibial cortical bone (relCt.Po100μm-tibia) indicated higher Tb.SpFN (R2 = 0.36, p < 0.01) and lower Tb.NFN (R2 = 0.45, p < 0.01). Bone resorption and structural decline of the femoral neck may be identified in vivo by measuring cortical bone thickness and large pores in the tibia. A lower thickness and the accumulation of large pores in the cortical bone of the tibia were associated with factors that impair femur strength: cortical bone thinning and rarefaction of the trabecular architecture in the femoral neck. [Display omitted] •Femoral neck vBMD, cortical bone thickness and trabecular architecture are associated with human proximal femur strength•Thinner cortical bone in the tibia reflects thinner cortical bone and lower density and number of trabeculae in the femur neck•Large cortical bone pores in the tibia are associated with higher separation and lower number of trabeculae in the femur neck